Homing pigeons only navigate in air with intact environmental odours : A test of the olfactory activation hypothesis with GPS data loggers - Gagliardo, Anna; Ioalè, Paolo; Filannino, Caterina; Wikelski, Martin (My University, 2011)
A large body of evidence has shown that anosmic pigeons are impaired in their navigation. However, the role of odours in navigation is still subject to debate. While according to the olfactory navigation hypothesis homing pigeons possess a navigational map based on the distribution of environmental odours, the olfactory activation hypothesis proposes that odour perception is only needed to activate a navigational mechanism based on cues of another nature. Here we tested experimentally whether the perception of artificial odours is sufficient to allow pigeons to navigate, as expected from the olfactory activation hypothesis. We transported three groups of pigeons in air-tight containers to release sites 53 and 61 km from home in three different olfactory conditions. The Control group received natural environmental air; both the Pure Air and the Artificial Odour groups received pure air filtered through an active charcoal filter. Only the Artificial Odour group received additional puffs of artificial odours until release. We then released pigeons while recording their tracks with 1 Hz GPS data loggers. We also followed non-homing pigeons using an aerial data readout to a Cessna plane, allowing, for the first time, the tracking of non-homing homing pigeons. Within the first hour after release, the pigeons in both the Artificial Odour and the Pure Air group (receiving no environmental odours) showed impaired navigational performances at each release site. Our data provide evidence against an activation role of odours in navigation, and document that pigeons only navigate well when they perceive environmental odours.
Keywords: 570